The Relationship Between Perceived Organizational Support and Affective Commitment: A Social Identity Perspective. (February 2013) - Marique, Géraldine; Stinglhamber, Florence; Desmette, Donatienne; Caesens, Gaëtane; De Zanet, Fabrice
The present research examines how the social identity perspective contributes to a better understanding of the relationships between perceived organizational support, affective commitment, and employees' performance at work. Using a sample of 253 employees from an engineering company, Study 1 found that organizational identification partially mediates the relationship between perceived organizational support and affective commitment. The results of Study 1 also indicated that the relationship between perceived organizational support and organizational identification is moderated by organizational prestige. In Study 2, using a sample of 179 postal employees, the authors replicated the mediating role of organizational identification in the relationship between perceived organizational support and affective commitment and found that affective commitment mediates the relationship between organizational identification and supervisor's ratings of extra-role performance.